2017
DOI: 10.7717/peerj.3933
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effect of nicotine in Parkinson’s disease models is associated with inhibiting PARP-1 and caspase-3 cleavage

Abstract: Clinical evidence points to neuroprotective effects of smoking in Parkinson’s disease (PD), but the molecular mechanisms remain unclear. We investigated the pharmacological pathways involved in these neuroprotective effects, which could provide novel ideas for developing targeted neuroprotective treatments for PD. We used the ETC complex I inhibitor methylpyridinium ion (MPP+) to induce cell death in SH-SY5Y cells as a cellular model for PD and found that nicotine inhibits cell death. Using choline as a nicoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…Apoptosis is regulated in part by Bcl-2 genes that regulate cell survival 27 . Reduced apoptosis and neuroprotective effect of NIC is marked by reduced cleavage of PARP-1 28 , 29 . NIC treatment resulted into a significant increase in Bcl-2 expression that reduced upon DZNepA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis is regulated in part by Bcl-2 genes that regulate cell survival 27 . Reduced apoptosis and neuroprotective effect of NIC is marked by reduced cleavage of PARP-1 28 , 29 . NIC treatment resulted into a significant increase in Bcl-2 expression that reduced upon DZNepA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In support of nicotine functioning as a neuroprotectant, several studies have identified different biochemical responses to nicotine that could contribute to its neuroprotective effects in CNS, including increased expression of growth/trophic factors such as NGF and FGF (Belluardo et al,2000, Garrido et al, 2003; Harrod et al, 2011; Takarada et al, 2012), decreased nitric oxide generation (Shimohama et al, 1996, Toborek et al, 2000), decreased arachidonic acid release (Marin et., 1997; Toborek et al,2000) and decreased caspase signalling (Lu et al, 2017). Further increased expression/activation of ERK1/2 has been shown in PC12 cells (Nakayama et al, 2001) and spinal cord neurons (Toborek et al,2007), which is attributed to nicotine-mediated neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…First, nicotine can prevent aggregation of both wild-type and A53T mutant α-synuclein in tubes [ 181 ]. Second, in several cell culture models of PD, nicotine treatment can significantly decrease cell loss [ 182 , 183 ]. Finally, in both 6-OHDA-induced rodent and MPTP-induced primate models of PD, nicotine administration can slow down dopamine neuron degeneration [ 184 , 185 ].…”
Section: Nicotine As a Drug Candidate For Pd Treatmentmentioning
confidence: 99%